Stuart Cloete's construction of Voortrekker religion in Turning Wheels - F. Hale (Acta Theologica)
Stuart Cloete’s novel of 1937, Turning Wheels, was unquestionably the most controversial of many fictional reconstructions of the Great Trek, a book which fell foul of Afrikaner nationalism and whose further importation into the Union of South Africa was long consequently banned. Religious motifs reflecting the popularised Calvinism of the Voortrekkers figure prominently in the text. Cloete depicted these migrants as people of faith whose removal to a new Canaan entailed both internal strife and repeated clashes with indigenous African tribes. Among the thematic elements are belief in divine purpose and providence, postfigurative uses of the Pentateuchal characters Moses and Abraham, the image of the clergy, the failure of religious belief to maintain ethical norms among the Voortrekkers and the contribution of an ethnocentric distortion of Christianity to disharmonious relations with black Africans.